2008
DOI: 10.1016/j.schres.2008.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Reduced interhemispheric connectivity in schizophrenia-tractography based segmentation of the corpus callosum

Abstract: Background A reduction in interhemispheric connectivity is thought to contribute to the etiology of schizophrenia. Diffusion Tensor Imaging (DTI) measures the diffusion of water and can be used to describe the integrity of the corpus callosum white matter tracts, thereby providing information concerning possible interhemispheric connectivity abnormalities. Previous DTI studies in schizophrenia are inconsistent in reporting decreased Fractional Anisotropy (FA), a measure of anisotropic diffusion, within differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 49 publications
4
76
1
Order By: Relevance
“…Not accounted for in these analyses are the few negative studies that exist. Two previous studies reported no differences in FA throughout the brain (Foong et al, 2002;Murakami et al, 2011); others have reported widespread lower FA but did not detect significant differences in the genu of the corpus callosum specifically (Agartz et al, 2001;Foong et al, 2000;Karlsgodt et al, 2008;Kubicki et al, 2008;Seal et al, 2008).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Not accounted for in these analyses are the few negative studies that exist. Two previous studies reported no differences in FA throughout the brain (Foong et al, 2002;Murakami et al, 2011); others have reported widespread lower FA but did not detect significant differences in the genu of the corpus callosum specifically (Agartz et al, 2001;Foong et al, 2000;Karlsgodt et al, 2008;Kubicki et al, 2008;Seal et al, 2008).…”
Section: Discussionmentioning
confidence: 77%
“…Postmortem studies have shown a genderdiagnosis effect of reduced axonal number (Highley et al, 1999a), oligodendrocyte density loss (Hof et al, 2003), and lower levels of immunoreactivity of oligodendrocyte-associated proteins in the genu of the corpus callosum (Flynn et al, 2003). Diffusion-weighted imaging has been relatively consistent in reporting reduced callosal FA in chronic schizophrenia (Douaud et al, 2007;Koch et al, 2010;Kubicki et al, 2008;Miyata et al, 2010;Mori et al, 2007b;RotarskaJagiela et al, 2008), including during remission (Koch et al, 2010) and less consistently in studies examining individuals at the first episode (Cheung et al, 2008;Gasparotti et al, 2009;Perez-Iglesias et al, 2010b;Peters et al, 2008;Price et al, 2005;Szeszko et al, 2005) or in earlier stages of illness (Davenport et al, 2010;Douaud et al, 2007;Kyriakopoulos and Frangou, 2009). Directly comparing first episode and chronic groups supports more severe changes in FA in the genu of the corpus callosum (Friedman et al, 2008;Kong et al, 2011), the left ILF (Friedman et al, 2008), and ALIC (Bora et al, 2011) in the chronic group including relative to the first episode group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 A study of patients with chronic schizophrenia also reported similar results: specifically, that fractional anisotropy decreased in the areas of the corpus callosum interconnecting with frontal regions and that the integrity of the anterior corpus callosum was significantly correlated with negative and positive symptoms. 41 Mitelman and colleagues 35,42,43 found that patients with schizophrenia and poor outcomes showed greater decline in fractional anisotropy and smaller corpus callosum size compared with patients with good outcomes. All these studies suggest that fractional anisotropy values may be an indicator of illness severity and outcome in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…17 Further, interhemispheric connections form a major portion of the functional connectivity in the resting brain 18 ; aberrant interhemispheric connectivity has also been prominently observed in schizophrenia. 19,20 Despite this consistency, there is a significant heterogeneity among patients in both the degree and the distribution of dysconnectivity. So far, it is unclear whether common mechanistic factors underlie the distributed pattern of dysconnectivity observed in patients.…”
Section: Introductionmentioning
confidence: 99%